Hydrogen materials science and chemistry of metal hydrides - NATO Advanced Research Workshop on Hydrogen Materials Science and Chemistry of Metal Hydrides (1999 : Katisiveli, Ukraine); Hampton, Michael D.; North Atlantic Treaty Organization. Scientific Affairs Division (Dordrecht : Kluwer Academic Publishers, 2002)
42